Blinatumomab Pharmacodynamics and Exposure–Response Relationships in Relapsed/Refractory Acute Lymphoblastic Leukemia. (18th September 2017) - Zhu, Min; Kratzer, Andrea; Johnson, Jessica; Holland, Chris; Brandl, Christian; Singh, Indrajeet; Wolf, Andreas; Doshi, Sameer
Abstract: We evaluated blinatumomab pharmacokinetics, pharmacodynamics (CD3+ T‐cell, CD19+ B‐cell, and cytokine levels), and their associations with efficacy or safety in relapsed/refractory acute lymphoblastic leukemia. Blinatumomab pharmacokinetics (continuous intravenous infusion) from a phase 2 study (n = 189; NCT01466179) were assessed noncompartmentally. Associations between steady‐state concentration (Css ) and efficacy (complete remission [CR] or CR with partial hematologic recovery [CRh]) or safety (cytokine release syndrome [CRS] and neurologic events [NEs]) were evaluated with statistical models. Blinatumomab mean ± SD Css was 621 ± 502 pg/mL (28 μg/day dose). Cytokines were transiently elevated in >50% of patients; B‐cell levels decreased in most patients. Lower B‐cell and bone marrow (BM) blast percentages and higher T‐cell percentages were associated with higher CR/CRh ( P < .001) in univariate analysis. Higher Css (OR, 1.90; 95%CI, 1.12‒3.21), higher peak IL‐10 level (1.59; 1.13‒2.22), and lower BM blast percentage (0.78; 0.69‒0.89) were associated with higher CR/CRh in multivariate analysis. Higher Css (HR, 1.40; 1.01–1.94) and lower B‐cell level (0.90; 0.84‒0.97) were associated with shorter time to NEs. Cytokine peaks were not associated with NEs or CRS. In conclusion, blinatumomab led to T cell‐mediated depletion of target B cells in blood and blasts in the bone marrow. Immune system effectiveness was important for treatment responses.